Pijat Bayi Modern Meningkatkan Kualitas Tidur Bayi Di Baby SPA Kota Palangka Raya - Yeni Lucin (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2018)
Introduction Infancy is a golden period for children's growth and development so it needs special attention. One of the factors that influence baby's growth is sleep and rest. With good sleep quality, baby's growth and development can be achieved optimally. Babies aged three to six months spend 14-15 hours sleeping. Objective To find out the quality of baby's sleep before and after a massage. The research design of this study used adesign Pre-experimental, with the design of the One-Group Pretest-Posttest Design, in this design there was a pretest before being treated. Thus the results of treatment can be known more accurately, because it can compare with the situation before being given treatment. Results With a sample of 17 babies. Using the Nonparametric test McNemar test obtained significant results which is 0.008 (<0.05) which means there is an effect of infant massage on the quality of infant sleep.